2022
DOI: 10.3390/educsci12120922
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face or Online Learning in Applied Statistics in Health Sciences? Failed Experiment or Opportunity after COVID-19?

Abstract: The rapid spread of the COVID-19 worldwide led to the migration of the traditional education system based on the face-to-face classroom into an improvised online system, among many other preventive measures. Thus, all teaching methods had to be adapted to this new modality. This work is aimed at studying the viability of the online teaching of the subject of Applied Statistics in Health Sciences in higher education based on the teaching experience lived during COVID-19. In addition to this, possible technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Pika and Reddy's findings indicate that home conditions, individual characteristics, pre-COVID-19 blended learning experiences, university training and support, teaching, learning, assessment practices, and policies altogether contributed to the exclusion of low-income students from active teaching and learning, equipping middleclass students with better chances of success compared to working-class students, and distressing female students and lecturers more than it distressed their male counterparts. A study from Spain [19] studied the viability of the online teaching of the subject of applied statistics in health sciences in higher education. Gutiérrez and colleagues showed that online teaching was feasible for the subject under study, although face-to-face learning continued to be reverted to a significant degree in favor of the quality of teaching.…”
mentioning
confidence: 99%
“…Pika and Reddy's findings indicate that home conditions, individual characteristics, pre-COVID-19 blended learning experiences, university training and support, teaching, learning, assessment practices, and policies altogether contributed to the exclusion of low-income students from active teaching and learning, equipping middleclass students with better chances of success compared to working-class students, and distressing female students and lecturers more than it distressed their male counterparts. A study from Spain [19] studied the viability of the online teaching of the subject of applied statistics in health sciences in higher education. Gutiérrez and colleagues showed that online teaching was feasible for the subject under study, although face-to-face learning continued to be reverted to a significant degree in favor of the quality of teaching.…”
mentioning
confidence: 99%